Design and development a cooker and inner coat isolator for peanuts - Siti Nur Amirah Abdullah (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The main purpose of this project is design and develop a cooker and inner coat isolator for peanuts. The aim of this project is to design and develop a product which able to cook and separate inner red skin of peanuts. Second objective is to design, choose and evaluate an apprpriate structure for cooker and isolates coat layer of peanut machine and last one is to produce a prototype and to test the functioning of the mechanical part of the product.